Women of the Sea:: performative practices as a critique of Brazilian patriarchal colonial myths - Araujo Auip, Marie; Aurélio Bulhões Martins, Marcos (Revista Brasileira de Estudos da Presença, 2024)
Women of the Sea: performative practices as a critique of Brazilian patriarchal colonial myths – The text analyses the Mulheres do Mar (Women of the Sea) project, conducted with elderly women from the Serviluz community in Fortaleza (CE). Through performance workshops, the colonial myth Iracema, by José de Alencar, was challenged. Feminist analyses in conjunction with Diana Taylor’s approach to archives and repertoires underpin the critique of the novel. Next, aspects of the methodological approach to creation are shared, with an emphasis on cartographies of the self. It reflects on how the collective development of a counter-narrative to the patriarchal heritage summarised in Iracema contributes to the debate on decolonial artistic-pedagogical practices.